Outcome of primary endoscopic dacrocystorhinostomy with and without stent: a randomised prospective study - Pandey, Rajesh; Yadav, Pramod Kumar; Patel, Amit Kumar; Rani, Poonam (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2017)
Background: The introduction of endoscopes with different degrees of angulation for endoscopic sinus surgery led to widespread use of endoscopic endonasal DCR (EDCR). The results of EDCR are not only encouraging, but are associated with many other additional advantages. Many modifications like LASER assisted endoscopic DCR, use of silicon tube for stenting, mitomycin-C application etc. have been described. However, insertion of silicon stent in endonasal DCR is most commonly used procedure. Many surgeons claim that use of silicon stent improves success rate of endoscopic DCR. On the other hand, some studies indicate that silicon stent itself is a reason for surgical failure. The present study was done to compare surgical outcome and complication of endoscopic DCR with and without silicon stent. Methods: 70 cases (total 90 EDCR) randomly taken for study. In 35 EDCR cases lacrimal stent were used and in 55 EDCR cases stent were not used. Success rate in both group was analysed using chi-square test. P value <0.05 was considered as significant. Results: We found a success rate of 90.9% and 85.7% for group A (stent not used) and group B (stent used) respectively. The statistic evaluation among these groups does not show any significant difference (p=0.445) which means that insertion of stent in cases of primary EDCR does not significantly change the surgical outcome. Conclusions: Endonasal DCR without silicon stent is considering as effective, safe and minimally invasive primary procedure for treatment of nasolacrimal duct obstruction. Role of using stent in primary EDCR is not very promising because it is not improving the outcome of surgery.